Networks of Military Alliances, Wars, and International Trade - Matthew O. Jackson; Stephen Nei (Fondazione Eni Enrico Mattei (FEEM), 2014)
We investigate the role of networks of military alliances in preventing or encouraging wars between groups of countries. A country is vulnerable to attack if there is some fully-allied group of countries that can defeat that country and its (remaining) allies based on a function of their collective military strengths. Even with such a demanding notion of vulnerability, we show that there do not exist any networks that are stable against the addition and deletion of alliances. We then show that economic benefits from international trade can provide incentives to form alliances in ways that restore stability and prevent wars. In closing, we briefly examine the historical data on interstate wars and trade, noting that a dramatic (more than ten-fold) drop in the rate of interstate wars since 1960 is paralleled by an unprecedented growth in trade over the same period.
Keywords: D74; D85; F10; 330; Alliances; Conflict; War; Networks; International Trade; Treaties